(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the political awareness of kindergarten children, as the research sample included (200) male and female kindergarten children in the Baghdad governorate. Political (19) paragraphs divided into ten concepts, namely: (Iraq flag, the capital of Iraq, the map of Iraq, the President of the Republic, the Iraqi army, coins, rivers of Iraq, antiquities of Iraq, elections, war, oil wealth, affiliation). Verification of the validity in two ways: apparent validity, and constructive validity, and the stability was extracted to test political awareness by the (retest) method, and (Vachronbach equation). The researcher reached the following conclusions: - Kindergarten children have political awareness, as the results came with an arithmetic mean higher than the hypothetical mean of the test In light of the research results, the researcher came up with a set of recommendations, including: Paying attention to providing the means and techniques that develop political awareness among kindergarten children, due to its importance in developing their future lives. Increasing the awareness of kindergarten educational staff of the importance of political awareness among kindergarten children through the establishment of training courses in preparation and training centers in the directorates of education and under the guidance of the Ministry of Education